Destruction of cultural heritage and armed conflicts. Focus on Africa - HERȚA, Laura-Maria (2025)
A great deal of literature focused on the transformation of warfare, thechanging nature of belligerence, as spurred by globalization and by theending of the Cold War bipolar order. Scholars1 theorized and analysed theso-called “new wars” and concentrated on the characteristics of intra-statearmed violence occurring at the beginning of the post-Cold War era. Othersemphasized the prevalence of civil wars.2 Many such approaches identifieda changing strategy in internal armed conflicts, by focusing on ethniccleansing, on systematic attacks carried out against unarmed civilians, onforced recruitment of children, on sexual violence carried out againstwomen, on forced displacement of populations, on deliberate attacks oncemeteries, cultural heritage, historic buildings, archives, places of worship,and on historical sites, in general. Therefore, the main arguments presentedin this book revolve around a changing dynamic and strategy in recent andcontemporary armed conflicts, which are internal (not international) andwhich feature attacks on civilians, on communities, on the links of ethnic, religious, identity groups (in general) to certain geographic areas or thesocial and historical developments in some territories.